â€œFamilyâ€ as a Site of Gender and Class Struggles in Catherine Limâ€™s The Song of Silver Frond - Mulyani, Sri; Manggala, Simon Arsa; Nirwinastu, Diksita Galuh (OKARA: Jurnal Bahasa dan Sastra, 2022)
â€œFamilyâ€ in The Song of Silver Frond (TSOSF) functions as a site of gender and class struggles to challenge the Chinese yin-yang and nei-wai tradition. Continuities and transformations in Chinese familial practices result from complex socio-cultural-generational dynamics. "Family" becomes a battleground of gender and class struggles for the preservation and transformation of those familial traditions. Moreover, the dynamic of ethnicity also intersects with gender and class relations. The traditional Chinese familial practices follow two fundamental Confucian gender foundations: yin-yang and nei-wai. The yin-yang delineation privileges man versus woman. Meanwhile, the private/public distinction of nei-wai relegates the woman's place to the domestic sphere. By employing Post-Structural feminist perspectives focusing on gender intersectionality, this article examines how "family" becomes the site of ethnic-gender-class struggles in TSOSF. The articles revealed that some family members, both men, and women, continue to apply the traditional Confucian rules from generation to generation. However, other members challenge those traditional practices to contest gender and class inequalities to adapt to different sociocultural dynamics in Southeast Asian Society. Thus, this article has articulated the way TSOSF displays "family" as a site of gender and class struggle in Chinese familial practices.